Australian community pharmacy services: a survey of what people with chronic conditions and their carers use versus what they consider important. Issue 12 (8th December 2014) - McMillan, Sara S; Kelly, Fiona; Sav, Adem; King, Michelle A; Whitty, Jennifer A; Wheeler, Amanda J
Abstract : Objective: To explore the purpose/s for which people with chronic conditions and their carers use Australian community pharmacies, and compare this to what pharmacy services they consider important, from the perspectives of both consumers and pharmacists. Design: An exploratory study involving a survey, which asked participants to indicate the pharmacy services they had ever used, and rate the importance of 22 pharmacy services to them, or the person they care for, or for their consumers if a pharmacist. Setting: Four regions of Australia: Logan-Beaudesert and Mt Isa/North West region, Queensland, Northern Rivers, New South Wales, and the Greater Perth area, Western Australia. Participants: Surveys were undertaken with 602 consumers and 91 community pharmacists. Results: Community pharmacy is predominantly used to obtain advice about medication and whether a doctor's visit is necessary, as well as for monitoring and screening services. Pharmacy services that were patient centric were important, such as individualised medication advice and respectful care, as well as tools or procedures to facilitate streamlined medication access. Less important services included adult vaccinations and health and wellness programmes. Carers identified services that assisted them with their specific role/s to be important. Overall, community pharmacists had a good understanding of the services that were important to people with chronic conditions and their carers. Conclusions: People with chronic conditions and their carers not only care about what services are delivered, but how they are delivered; they sought services that generally improved their access to medication and information, but in a way that was patient centred. Ultimately, pharmacists understood the importance of patient-centred care for people with chronic conditions and their carers, perhaps indicating a greater acceptance of integrating patient-centred care into their everyday practice.